Altered spectra of hypermutation in antibodies from mice deficient for the DNA mismatch repair protein PMS2 - Winter, David B. (The National Academy of Sciences, 1998)
Mutations are introduced into rearranged Ig variable genes at a frequency of 10(−2) mutations per base pair by an unknown mechanism. Assuming that DNA repair pathways generate or remove mutations, the frequency and pattern of mutation will be different in variable genes from mice defective in repair. Therefore, hypermutation was studied in mice deficient for either the DNA nucleotide excision repair gene Xpa or the mismatch repair gene Pms2. High levels of mutation were found in variable genes from XPA-deficient and PMS2-deficient mice, indicating that neither nucleotide excision repair nor mismatch repair pathways generate hypermutation. However, variable genes from PMS2-deficient mice had significantly more adjacent base substitutions than genes from wild-type or XPA-deficient mice. By using a biochemical assay, we confirmed that tandem mispairs were repaired by wild-type cells but not by Pms2(−/−) human or murine cells. The data indicate that tandem substitutions are produced by the hypermutation mechanism and then processed by a PMS2-dependent pathway.